The Sociological Approach in Qur’anic Interpretation: An Analysis of Fazlur Rahman’s Double Movement Method - Ahmad Fawaid; Abd Wahid; Usman (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
This study aims to analyze the sociological approach in Qur’anic interpretation through the double movement method developed by Fazlur Rahman. The focus of the study is directed toward three main issues: first, the methodological framework of the double movement in the process of Qur’anic interpretation; second, the ways in which this method represents a sociological approach to the Qur’an; and third, the extent to which the double movement method is relevant for analyzing contemporary social problems. This research employs a qualitative approach with a library-based research design, using primary data from Fazlur Rahman’s works and scholarly journal articles that discuss contextual and social approaches to Qur’anic interpretation. Data analysis is conducted through descriptive-analytical techniques and contextual hermeneutical analysis. The findings indicate that the double movement method has a systematic methodological framework, consisting of an interpretive movement from the socio-historical context of revelation toward the formulation of universal moral principles, followed by an applicative movement that projects these principles into contemporary social contexts. This method represents a sociological approach to the Qur’an by emphasizing the analysis of social realities as a fundamental basis for understanding the text, thereby positioning the Qur’an as a revelation that actively engages with human social problems. Furthermore, the double movement method is highly relevant for analyzing various modern social issues, such as social justice, pluralism, gender relations, and public ethics, as it effectively bridges the normative values of the Qur’an with the dynamics of modern society.